A biographical dictionary of civil engineers in Great Britain and Ireland. Volume 1, - Skempton, A. W. (Thomas Telford, 2002)
This biographical reference work looks specifically at the lives, works and careers of those individuals involved in civil engineering whose careers began before 1830.